2017
DOI: 10.1038/s41598-017-14983-9
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency pulsed electromagnetic fields cause antioxidative defense mechanisms in human osteoblasts via induction of •O2 − and H2O2

Abstract: Recently, we identified a specific extremely low-frequency pulsed electromagnetic field (ELF-PEMF) that supports human osteoblast (hOBs) function in an ERK1/2-dependent manner, suggesting reactive oxygen species (ROS) being key regulators in this process. Thus, this study aimed at investigating how ELF-PEMF exposure can modulate hOBs function via ROS. Our results show that single exposure to ELF-PEMF induced ROS production in hOBs, without reducing intracellular glutathione. Repetitive exposure (>3) to ELF-PEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 43 publications
(60 reference statements)
8
92
0
Order By: Relevance
“…We found SOD and p53 were increased to combat ROS increasing. Our results seem to support the report of Ehnert et al, that extremely low-frequency electromagnetic fields cause antioxidant defense mechanisms [66].…”
Section: Differentiationsupporting
confidence: 93%
“…We found SOD and p53 were increased to combat ROS increasing. Our results seem to support the report of Ehnert et al, that extremely low-frequency electromagnetic fields cause antioxidant defense mechanisms [66].…”
Section: Differentiationsupporting
confidence: 93%
“…On the contrary, but possibly consistent with a proliferative phenotype, ALP activity and Osteocalcin expression were decreased in cultures exposed to PEMFs [Lin and Lin, ]. Increased resistance to oxidative stress was further investigated in a recent study by Ehnert et al [] using primary human osteoblasts (hOBs) exposed to 0.6 Hz, 0.28 mT PEMF bursts of 16 Hz pulses for 7 min/day, using a stimulation regime that was shown to be able to increase cell differentiation in the same cell model [Ehnert et al, ]. The authors demonstrated that EMFs induced the generation of Reactive Oxygen Species (ROS) in hOBs, most noticeably O 2 − (superoxide anion) and H 2 O 2 (hydrogen peroxide), and also induced the expression of antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase.…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%
“…The authors demonstrated that EMFs induced the generation of Reactive Oxygen Species (ROS) in hOBs, most noticeably O 2 − (superoxide anion) and H 2 O 2 (hydrogen peroxide), and also induced the expression of antioxidant enzymes superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase. Most interestingly, they showed that the induction of non‐toxic levels of ROS was required for PEMF‐induced osteoblast differentiation [Ehnert et al, ].…”
Section: Effects Of Pemfs On Osteoblastsmentioning
confidence: 99%
“…Ehnert et al identified a specific extremely low-frequency pulsed electromagnetic field (ELFPEMF) (10 to 90.6 Hz) that supports human osteoblast function in an ERK1/2-dependent manner. The ELF-PEMF by producing non-toxic amounts of reactive oxygen species (ROS), induced antioxidative defense mechanisms in these cells [63, 64]. …”
Section: Physical Stimulation For Bone Regeneration and Fracture Healingmentioning
confidence: 99%